Indigenous Conceptions of Well-Being: Rejecting Poverty, Pursuing Mino-Bimaadiziwin - Denis, Jeffrey S.; Duhaime, Gérard; Newhouse, David (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2017)
According to conventional metrics, such as the low-income cut-off and social assistance rates, Indigenous peoples in Canada have disproportionately high levels of poverty. But what does poverty mean from an Indigenous perspective? Drawing on data from the Poverty Action Research Project (PARP) — a five-year partnership between academic researchers, the Assembly of First Nations, and five First Nations communities in different regions of Canada seeking to reduce poverty and improve community health — this paper examines the relational and subjective aspects of poverty and well-being. Our analysis of PARP communities' discussions of poverty and actions to address it suggests that poverty is seen through the lens of what the Anishinaabek call Mino-Bimaadiziwin, which describes "living well" in a holistic, multidimensional, and community-centered sense. Interventions to address poverty therefore would be better framed as initiatives to enable the pursuit of a good life, as Indigenous people understand it, and must consider not only the economic impacts, but also the interrelated environmental, political, intellectual, social, emotional, spiritual, and cultural dimensions.